Book Review: Zoltan J. Acs (Ed.), The Knowledge Spillover Theory of Entrepreneurship. (March 2015) - Cunningham, James
Zoltan J. Acs (Ed.), The Knowledge Spillover Theory of Entrepreneurship, Cheltenham, UK: Edward Elgar Publishing, 2010, 683 pp.